THE RELATIONSHIP BETWEEN ACCURACY OF MEDICAL TERMINOLOGY DOCUMENTATION AND DIAGNOSTIC CODE ACCURACY IN OBSTETRIC CASES AT RSIA PURI MALANG - Alvionita, Chyntia Vicky; Zein, Eiska Rohmania (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
The Accurate medical documentation and diagnostic coding are essential components of healthcare services, directly influencing the quality of patient care, health data reporting, and hospital reimbursement systems. Therefore, this study aims to identify the relationship between the accuracy of medical terminology documentation and diagnosis code accuracy, providing insights for improvement in coding systems at hospitals. This study uses a quantitative, cross-sectional approach to examine the relationship between the accuracy of medical terminology documentation and diagnosis coding in Obstetric cases. The research was conducted in 2024 at RSIA Puri Malang. Data were collected from 300 medical records through simple random sampling. Descriptive statistics were used to analyze the accuracy of documentation and coding, followed by a chi-square test to assess the correlation between medical terminology accuracy and diagnosis coding precision. The study shows a statistically significant relationship between the accuracy of medical terminology documentation and diagnosis coding accuracy in Obstetric cases, with a p-value of 0.048. Since the p-value is less than the significance level of 0.05, this indicates that the observed relationship is unlikely to be due to chance, supporting the hypothesis that accurate medical terminology documentation positively impacts the precision of diagnosis coding. The findings suggest that improving the quality of documentation can lead to more accurate coding, which is crucial for effective healthcare delivery, billing processes, and insurance claims.